The interpretation of the lyrics of Seiza ni Naretara from the Anime Bocchi the Rock! Based on Michael Riffaterre's semiotic analysis - Habibulloh, Muhammad Azis; Noviana, Fajria (Japanese Research on Linguistics, Literature, and Culture, 2024)
Seiza ni Naretara is a soundtrack from the anime Bocchi The Rock!. The song tells the story of the desire to become a constellation. Although soundtracks are typically tailored to the storyline of the film, interestingly, the story of Bocchi The Rock!! does not involve stars or constellations. This peculiarity sparked the author's interest in exploring the deeper meaning behind the song. To analyze it, Riffaterre's semiotics of poetry theory was used. Through heuristic and hermeneutic readings, as well as an intertextual study, the findings reveal that the song conveys a sense of self-discrepancy.